PERANCANGAN ULANG FASILITAS PRODUKSI BERBASIS SYSTEMATIC LAYOUT PLANNING DAN BLOCPLAN PADA PT MUHAYYA CILEGON STEEL - Abdulgani, Muhamad Fiqih; Sopyan, Sofhan; Ramadhan, Virgi; Mubaraq, Ibnu; Prabowo, Dimas Rakha; Meylandri , Raffi Trie; Maulana, Adriyan; Rini, Asih Setyo (JURNAL LOGISTICA, 2026)
Unplanned facility layout is the main cause of operational inefficiency at PT Muhayya Cilegon Steel, a steel plate processing manufacturer established in 2024 in Cilegon, Banten, Indonesia. Based on field observations conducted in March 2026, this company faces four fundamental problems: unverified location placement, 2.30% non-value-added activities, unstructured floor space calculation, and material backtracking caused by machines placed out of process sequence. This study applies the Systematic Layout Planning (SLP) approach in an integrated manner. The stages include Factor Rating and Transportation methods, Operation Process Chart (OPC), Flow Process Chart (FPC), Activity Relationship Chart (ARC) analysis, and layout redesign using BLOCPLAN-90 software. The results prove Cilegon as the optimal location with the highest Factor Rating score of 4.25. The Least Cost method generates a distribution cost of Rp585,000,000, representing 7.5% efficiency improvement compared to the North West Corner method. The total floor space requirement is 168.991 m². BLOCPLAN Layout 6 was selected as the best layout with an Adjacency Score of 0.82 and Product Movement of 387, successfully eliminating backtracking in the existing conditions and fulfilling all critical adjacency relationships defined in the ARC.